The influence of passenger satisfaction on relationship formation in the South African domestic airline industry - C. F. De Meyer; P. G. Mostert (South African Journal of Business Management, 2011)
Customers are increasingly becoming aware of alternative offerings in the market place, and are thus more demanding in terms of their expectations pertaining to service delivery. As airlines in particular are vulnerable to competitors' offerings, they should offer passengers high levels of service and ensure that passengers are satisfied with their service offering in an effort to build long-term relationships. Building long-term relationships is important due to the financial and social benefits it holds to both the business and its customer. This study investigates whether passenger satisfaction influences whether or not passengers have formed a long-term relationship with the airline they fly with most often. Data was collected from South African domestic passengers departing from OR Tambo International Airport in Johannesburg by means of a convenience sample. Main findings from the study indicate that the majority of dissatisfied respondents have not formed a long-term relationship with the domestic airline, while satisfied respondents are more inclined to form a long-term relationship.
Keywords: 650